WTP5.1 Perioperative hypothermia in elective surgical patients - Arifuzaman, Mohammed; Shah, Jigar; Bhattacharya, Sayan (British journal of surgery, 2023)
Introduction Perioperative hypothermia is an under-reported, yet well recognized complication of surgery. Normal thermoregulatory mechanisms are disrupted in anesthetized patients. Up to 70% of surgical patients develop perioperative hypothermia, with serious consequences including coagulopathy, sepsis and cardiac events. Methods In this single centre study, we collected prospective data from 100 elective operations in urology, gynaecology, general and breast surgery. The pre-operative, pre-induction, intraoperative, post-procedure and in recovery temperatures (in Celsius) were recorded. Any temperature below the 36°C was regarded as hypothermia and the total incidence of hypothermia during all the 5 phases were calculated. Results Incidences of hypothermia in pre-operative, pre-induction, intraoperative, post-procedure and in-recovery were 4 %, 5%, 12 %, 11 %, 8 % and 6 % respectively. Multiple regression analysis of pre-operative, pre-induction and intra-operative temperatures resulted in a p value of 0.237 for pre-operative temperature and 0.000032577 for pre-induction temperatures respectively. This suggests that pre-induction temperature was the most statistically significant parameter for intra-operative hypothermia. Furthermore, regression analysis predicted the intra-operative temperature for a given pre-induction temperature. Regression analysis line fit plot between preinduction and intra-operative temperatures predicted that for intraoperative temperature to be 36.74 °C, mean preinduction temperature is to be raised to 37.2 °C. Conclusion This study highlights the incidence of intraoperative hypothermia and need for active interventions to prevent the same. It paves the way for a single blinded randomized controlled trial for comparing different modalities to pre-warm patients and prevent intraoperative hypothermia.